Pengaruh Corporate Social Responsibility Disclosure Terhadap Kinerja Keuangan Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Febrianawati; Windi Pratiwi (Jurnal Equilibrium Manajemen Fakultas Ekonomi Universitas Panca Bhakti, 2023)
The aim of this research is to analyze the influence of Corporate Social Responsibility Disclosure on Company Financial Performance. The research object used is the banking industry with a total of 60 companies listed on the Indonesia Stock Exchange (BEI) in 2010 - 2012. The independent variable in this research is corporate social responsibility disclosure, the dependent variables are return on equity (ROE) and Return on Assets (ROA). The data analysis technique used is simple regression analysis. The results of this research indicate that Corporate Social Responsibility Disclosure has no effect on ROA with a significance value of 0.672 > 0.05. Meanwhile, the influence of Corporate Social Responsibility Disclosure on ROE has a significance value of 0.033 <0.05, which means that Corporate Social Responsibility Disclosure has an effect on ROE.